Análise da vegetação e organismos edáficos em área de caatinga na Serra da Caiçara, Maravilha, Alagoas - Silva , Leila Caroline Salustiano (2017)
The biome Caatinga presents numerous landscapes considered unique, of which little is known, of different types, those located forests in hills and plateaus of the semiarid region, locally known as Brejo de Altitude which have different characteristics from the climate perspective, edaphic, topographic, floristic , physiognomy and diverse fauna which little is known. In Alagoas, we highlight the Brejo de Altitude located in the municipality of Maravilha, already in the process of degradation and without divulging research on fauna and flora. The general objective of this research was to analyze the shrub-tree component and the diversity and uniformity of the edaphic organisms in the Caatinga area, located in the Serra da Caiçara, Alagoas. An experimental area was selected for collection from February to December 2016. The experimental area totals 1 ha divided in 100 x 10 m plot where the floristic and phytosociological survey was carried out. All living individuals with circumference (CAB ≥ 9 cm and height ≥ 1 m) were included. Twenty plots were selected for evaluating macrofauna and soil mesofauna, and soil temperature readings, soil water content, soil carbon and organic matter contents and rainfall measurement were used. The families with the greatest number of species in the shrub-tree stratum are: Fabaceae, Cactaceae, Euphorbiaceae, Anacardiaceae and Mimosaceae; The species with the highest number of individuals are: Anadenanthera colubrina (Vell.) Brenan var. Cebil (Angico de caroço), Syagrus coronata (Mart.) Becc. (Ouricuri), Manihot glaziovii Muell. Arg. (Maniçoba), Bauhinia cheilantha (Bong.) Steud (Mororó) and Laetia apetala Jacq (Pau piranha); The evaluated phytosociological parameters present important values in relation to the classes of height (m), diameter (cm) and total basal area (m²) and the other results are above the average found in Caatinga areas; The diversity index of Shannon-Weaver (H ') shows high richness for the Caatinga area of Serra da Caiçara, when compared to other Caatinga areas in the Brazilian Semiarid; The species with aggregated spatial distribution are: Bauhinia cheilantha (Bong.) Steud (Mororó), Cordia trichotoma (Vell.) Arrab. Ex Steud (Frei jorge), Mimosa cf. Malacocentra Mart (Rasga beiço), Randia armata (Sw.) DC. (Espinho de cruz branco), Xylosma sp. (Espinho de cruz roxo), Pau de rocha tipo 4 e Pau de rocha tipo 10; The Hymenoptera group is the most abundant of the edaphic macrofauna due to its ease of adaptation to the local conditions of the environment, as evidenced by the low rates of Shannon and Pielou; The dominant groups of the edaphic mesofauna are: Acarina (ácaro) and Collembola (Colêmbolo) demonstrated by low values of diversity and uniformity; The edaphoclimatic conditions influence the richness, abundance, diversity and uniformity of the organisms of the macrofauna and soil mesofauna; Serra da Caiçara has high floristic and faunistic diversity, which indicates that the area is preserved; The edaphic indicators of abundance, richness, diversity and uniformity recorded in the Serra da Caiçara stand out in relation to the other Brejos de altitude of the Brazilian Semiarid; The characteristics presented by the Classes of Diameter, Height Classes and Total Basal Area of the species sampled indicate that the Serra da Caiçara is a Brejo de Altitude.